PENERAPAN EVIDENCE BASED NURSING (EBN) AROMATERAPI LAVENDER DALAM MENGATASI KELELEHAN PERAWAT DI RUANG IGD 1 RUMAH SAKIT BHAYANGKARA TK.I R.SAID SUKANTO - Rahmadia (2023)
Nurses are responsible for administering all types of health care, including health promotion, disease prevention, treatment of physical and mental illness, care for the disabled, and community care for people of all ages. Nurse workload imbalance is a problem that often occurs in hospitals and often causes fatigue for nurses. fatigue can interfere with nurse performance which will then have an impact on the quality of service offered to clients and reduce patient satisfaction. Lavender aromatherapy is a method of relaxation to overcome work fatigue. Based on data collection from the 12 people in charge of the room, it was found that 5 nurses or 58.3% of the total were included in the less tired group, while 4 nurses or 33.3% were included in the tired category, and three people or 25% of the total were included in the fatigue category. very tired category. The intervention was carried out for 3 days from 13 March 2023 to 15 March 2023. The intervention was given to nurses in the tired and very tired categories with a total of 7 nurses. decreased fatigue level, namely as much as 85.71% of nurses (6 people) whose fatigue decreased to the less tired and very tired category became less tired and 14.28% of nurses (1 person) who were previously in the very tired category became tired. This shows that giving lavender aromatherapy can change the level of fatigue.